2019
DOI: 10.12688/f1000research.19279.2
|View full text |Cite
|
Sign up to set email alerts
|

Screening tuberculosis patients for diabetes mellitus in a routine program setting in Kampala, Uganda: a cross-sectional study

Abstract: Background: Uganda is located in East Africa and is among the countries with the lowest income globally. The ten health centres in this project serve populations in the under-privileged communities of Kampala. The objective of the study was to implement diabetes mellitus (DM) screening among tuberculosis (TB) patients in a routine program setting with limited resources and high human immunodeficiency virus (HIV) prevalence. Methods: A descriptive cross-sectional observational study was conducted in ten health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, the study reported that stigma due to TB disease, weak collaborative working culture among TB and DM clinics and financial challenges were among the barriers identified to be affecting implementation of effective integration of healthcare services. 48 On the other hand, a cross-sectional study that was conducted in Uganda 43 found that TB screening for DM in routine care was feasible, however, political will and programming issues were to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study reported that stigma due to TB disease, weak collaborative working culture among TB and DM clinics and financial challenges were among the barriers identified to be affecting implementation of effective integration of healthcare services. 48 On the other hand, a cross-sectional study that was conducted in Uganda 43 found that TB screening for DM in routine care was feasible, however, political will and programming issues were to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…10 The prevalence of diabetes in our health facility cases (3.8%) is also consistent with a larger study of TB patients in an outpatient setting in Kampala which found a 2.3% prevalence of diabetes. 11 Notably, studies of hospitalized patients from Uganda 7 and elsewhere in sub-Saharan Africa 12 have reported a much higher prevalence of diabetes -but these estimates may not reflect the burden of diabetes in the underlying community. While our estimate of overall diabetes prevalence is consistent with other studies in Uganda, our results may not reflect the contribution of diabetes to TB in Uganda as a whole, due to the young age distribution in the study population and the younger average age of individuals with prevalent compared to notified TB.…”
mentioning
confidence: 99%